Cardiovascular Risk Screening in A Rural Area in India and Markov Modelling for Cost Effectiveness - Newtonraj, Ariarathinam; Kannan, K Senthamarai (National Journal of Community Medicine, 2024)
Introduction: Cardiovascular diseases (CVDs) are the major cause of death in India. This study aimed to assess the CVDs risk factors in a remote rural area and its cost effectiveness Markov Model. Methods: Community based screening for known Hypertension, Diabetes and both were done. Basic Demography, health status assessment, Basic health related serum and blood analysis were done. Markov Modelling was done to assess the Cost effectiveness of the screening programme. Results: There were 7% of the participants having CVD risk of more than 40%, 3% with 30 to 40% risk, 11% were with 20-30% risk, 22% were with 10-20% risk and 57% were with less than 10% risk. In the higher risk group (>40% risk) participants with both ‘HTN and DM’ were having higher risk (11%). Participants with higher age, Female, Illiterate, Anaemia, lower per-capita income, both HTN and DM, smokers, Hypercholesterolemia, Hypothyroidism, and CKD were having higher CVDs risk of >40%. Markov analysis for active screening was shown to be highly cost-effective with the ICER value of INR 78730 per one unit of Quality Adjusted Life Year (QUALY) gained. Conclusion: Cardiovascular Diseases risk is higher among HTN and DM patients in the rural community in India. The screening and management at the community level are highly cost effective.